2002
DOI: 10.1097/00000658-200202000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical “Placebo” Controls

Abstract: Surgical placebo controls should be used only when no other trial design will yield the requisite data and should always be accompanied by a rigorous informed consent process and a careful consideration of the related risks and benefits. The recommended ethical guidelines were adopted as AMA ethics policy and are now incorporated in the AMA's Code of Medical Ethics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 11 publications
0
40
0
5
Order By: Relevance
“…Critics of sham procedures point out that the use of a procedure that could cause harm without offering a compensating physiologic benefit poses ethical problems and might violate the principle of nonmaleficence [22]. This has led renowned ethicist Ruth Macklin to conclude that "performing surgery in research subjects that has no potential of therapeutic benefit fails to minimize the risk of harm" [23].…”
Section: Sham Surgerymentioning
confidence: 99%
“…Critics of sham procedures point out that the use of a procedure that could cause harm without offering a compensating physiologic benefit poses ethical problems and might violate the principle of nonmaleficence [22]. This has led renowned ethicist Ruth Macklin to conclude that "performing surgery in research subjects that has no potential of therapeutic benefit fails to minimize the risk of harm" [23].…”
Section: Sham Surgerymentioning
confidence: 99%
“…They have shown that the Moseley study [8] for arthroscopy in OA (which was shown to be useless) saved a large amount of money at a saving of approximately $ 5000 a procedure in the United States. The Council for Judicial and Ethical Affairs (CJEA) of the American Medical Association report which went into question of sham surgery made several important recommendations, [26] They recommended among other things, that sham surgery should be used only if there is no other trial design that will generate the required data, the informed consent process should be rigorous, and pointed out that sham operations are unjustified to test minor modifications of existing procedures.…”
Section: The Question Of Sham Operationsmentioning
confidence: 99%
“…Moseley et al [21]could prove that there is no difference in pain relief after arthroscopic or placebo surgery for osteoarthritis of the knee. This led to a first version of ethical guidelines on the use of surgical placebo controls in the design of surgical trials [22]. If no sham operation is performed, investigators should be aware of bias through the placebo effect of all surgical procedures [23].…”
Section: Specific Problems Of Randomized Controlled Studies In Surgerymentioning
confidence: 99%